(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The Middle East in general and the Muslim world in particular has been plagued by cultural ravaging, imperial interests, and unequal partnership with the West, especially with the United States. However, since 2001, the Arab world has moved to the centre of cultural debates and received the major number of cultural misrepresentations in American films. This study explores the significant role of movies in presenting distorted information and creating irrefutable images of the Arab world, its people, its religion, its culture, and its way of life. Analysis in this study investigates the assumption implicit in the conception that American films is in solidarity with the States ignoring its hegemony and imperial ambitions in the region and its saturation with imperial practices. In response to the terrorist attacks of 9/11, 2001, films have been one of the most effective mediums to represent the feelings of the American nation and the concern of the state. Therefore, this study will offer a different approach to the study of films, a semantic and semiotic analysis, in which cultural attitudes and political orientations of film directors allow movies to follow the mainstream politics and do not grapple with the hegemonic interests. Moreover, analysis in this study will contribute, in a good way, to suggesting a systematic approach to the study of post-9/11 American films in order to evaluate the communicative and aesthetic impact as a powerful cultural medium.